Estimating the sensitivity of CEO compensation to gross versus net accounting performance - Black, Dirk E.; Dikolli, Shane S.; Hofmann, Christian; Pfeiffer, Thomas (Contemporary Accounting Research, 2024)
Abstract In empirically estimating the relation between CEO compensation and accounting‐based firm and peer performance, researchers often define the performance variables net of CEO compensation expense. We analytically show that a researcher's use of CEO compensation as a regression's dependent variable and as an expense in defining a regression's independent variables representing accounting‐based firm and peer performance will bias the researcher's pay‐for‐performance and relative performance evaluation (RPE) regression coefficients. In a panel estimation of CEO compensation, we document an attenuation bias in the coefficients on net firm and net peer performance. This evidence may partially explain inferences of weak CEO incentives and limited usage of RPE in prior work. Our results imply that in CEO compensation regressions, a researcher can remove biases in inferring CEO incentives and RPE usage by using gross rather than net accounting performance variables—that is, by adding back CEO compensation expense to net accounting measures.